2010
DOI: 10.1002/cyto.b.20540
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric analysis of peripheral blood dendritic cells in patients with severe sepsis

Abstract: Background: Dendritic cells (DC) play a key role in cell-mediated immunity. We aimed to analyse the number and function of peripheral blood (PB) myeloid and plasmacytoid DC (mDC/pDC) in patients with severe sepsis.Methods: Twenty-six septic patients, 20 surgical patients (abdominal aortic aneurysm) and 20 healthy controls were enrolled in this prospective study.Results: At day 1 (enrollment in the study), septic patients showed in comparison with healthy controls, decreased mDC (P < 0.001) and increased pDC (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 43 publications
(60 reference statements)
1
27
0
1
Order By: Relevance
“…For two distinct populations of DCs, mDCs and pDCs, their numbers was markedly reduced in patients with sepsis when compared with controls, and both cell counts recovered slightly until day 28 [38]. But data from another clinical study of twenty-six patients showed that decreased mDC and increased pDC were observed at day 1, and the number of mDCs was not different in survivors and nonsurvivors of septic patients, while pDCs were obviously higher in nonsurvivors [39]. This discrepancy between these two study groups may be due to the different severity of illness.…”
Section: The Effect Of Sepsis On Dcs Numbersmentioning
confidence: 99%
See 1 more Smart Citation
“…For two distinct populations of DCs, mDCs and pDCs, their numbers was markedly reduced in patients with sepsis when compared with controls, and both cell counts recovered slightly until day 28 [38]. But data from another clinical study of twenty-six patients showed that decreased mDC and increased pDC were observed at day 1, and the number of mDCs was not different in survivors and nonsurvivors of septic patients, while pDCs were obviously higher in nonsurvivors [39]. This discrepancy between these two study groups may be due to the different severity of illness.…”
Section: The Effect Of Sepsis On Dcs Numbersmentioning
confidence: 99%
“…At day 28, the expression of HLA-DR on mDCs was recovered but remained lower than that in controls, while HLA-DR on pDCs showed a similar expression pattern to controls [38]. Besides HLA-DR, the percentage of CD83 and CD86 was also reported to be reduced in septic patients, but chemokine receptor CXCR4 was upregulated [39]. …”
Section: The Effect Of Sepsis On Dcs Functionmentioning
confidence: 99%
“…In mouse models of SS, several studies have shown that DC numbers are decreased in the blood as well as the tissue level (8)(9)(10)(11)(12)(13)(14). Apoptosis has been proposed to be the main mechanism responsible for these observations (15).…”
mentioning
confidence: 97%
“…There is accumulating evidence that a diminished expression of human leukocyte antigen-DR on circulating monocytes (mHLA-DR) measured by flow cytometry is considered a reliable indicator of immunosuppression in critically ill patients (36,37). It is also known that monocytes with low HLA-DR expression are known to be unable to mount a proinflammatory response to any subsequent bacterial challenge or to properly present antigens to T cells (37).…”
Section: Inter-laboratory Assessment Of Flow Cytometric Monocyte Hla-mentioning
confidence: 99%